HIPERTENSI PADA PASIEN PEREMPUAN: LAPORAN KASUS - Rahmi Zuraida; Dian Isti Angraini (Medula, 2026)
Hypertension is a chronic non-communicable disease and a major risk factor for cardiovascular complications. Poor treatment adherence and unhealthy lifestyle behaviors frequently contribute to inadequate blood pressure control. This case report aims to describe the comprehensive management of grade 2 hypertension in a 55-year-old female patient at a primary healthcare facility. Data were collected through history taking, physical examination, medical record review, and a three-week follow-up evaluation. The patient presented with intermittent headaches, numbness, and tingling sensations in both lower extremities. Physical examination revealed a blood pressure of 160/92 mmHg and a body mass index of 24.69 kg/m², classified as overweight. The patient had a five-year history of hypertension, poor medication adherence, a high-sodium diet, and insufficient physical activity. Based on clinical findings, the patient was diagnosed with uncontrolled grade 2 hypertension. Pharmacological treatment consisted of amlodipine 10 mg once daily and captopril 12.5 mg twice daily. Non-pharmacological interventions included health education regarding hypertension, medication adherence, sodium restriction, dietary improvement, increased physical activity, and regular blood pressure monitoring. Follow-up after three weeks demonstrated improvement in clinical symptoms, better treatment adherence, healthier lifestyle behaviors, and a reduction in blood pressure to 130/88 mmHg. This case highlights that a combination of pharmacological therapy, health education, and lifestyle modification plays an important role in achieving blood pressure targets and preventing long-term complications in patients with hypertension.